Fig. 18 in A late Paleocene fauna from shallow-water chemosynthesis-based ecosystems, Spitsbergen, Svalbard - Hryniewicz, Krzysztof; Amano, Kazutaka; Bitner, Maria Aleksandra; Hagström, Jonas; Kiel, Steffen; Klompmaker, Adiël A.; Mörs, Thomas; Robins, Cristina M.; Kaim, Andrzej (Zenodo, 2019)
Fig. 18. Hiatellid bivalve Cyrtodaria aff. rutupiensis (Morris, 1852) from the upper Paleocene, Basilika Formation, Zachariassendalen, Spitsbergen, Svalbard. NRM-PZ Mo 183943a–b, partial shell of a butterflied specimen with left (LV) and partial right valve (RV) preserved, showing external ornament of commarginal growth lines, and ridges on the inner shell surfaces supporting the posterior of anterior adductor muscle scar. Published as part of Hryniewicz, Krzysztof, Amano, Kazutaka, Bitner, Maria Aleksandra, Hagström, Jonas, Kiel, Steffen, Klompmaker, Adiël A., Mörs, Thomas, Robins, Cristina M. & Kaim, Andrzej, 2019, A late Paleocene fauna from shallow-water chemosynthesis-based ecosystems, Spitsbergen, Svalbard, pp. 101-141 in Acta Palaeontologica Polonica 64 (1) on page 123, DOI:10.4202/app.00554.2018, http://zenodo.org/record/10980900